Education Research and Audiovisual Production: The Emergence of Minor Stories in Postmedia Society - Armella, Julieta (2024)
The authors discuss findings from an educational research study carried out in a secondary school of the Buenos Aires Metropolitan Region based on creative research methods and on a collaborative audiovisual project. They inquire into the forms education takes in a postmedia society and they explore the possibilities of the school as time-space to reflect upon the world by means of experimenting with diverse languages and techniques. Here the authors analyze audiovisual materials produced by students and suggest three analytic categories—the scream, the testimony and the singular experience—which are related by an incident that took place in the students’ neighborhood, known as the “Carcova Massacre”. The authors hypothesize that when this event is narrated in the first person by the students—who witnessed the death of their two young neighbors—, the story reported by the media as a police incident becomes a minor story, making it a lived story.